Potret Komunikasi Antarbudaya Muslim dan Adat Aboge Mudal di Wonosobo - Asep Dadang Abdullah; Silvia Riskha Fabriar; Farida Rachmawati; Mafriha Azida (Jurnal Komunikasi Islam, 2023)
This study aims to explore a portrait of social communication in the Muslim community and the Aboge community in Binangun Hamlet, Mudal Village, Mojotengah District, Wonosobo Regency. This study is qualitative research using a sociological approach. Religious leaders, Aboge traditional leaders, as well as village heads in Mudal were decided to be key informants and primary data sources, while other various elements within both communities as secondary sources. The results illustrate that Muslim and the Aboge community communicate using verbal and nonverbal means, with primary, secondary, circular and omnidirectional network (star) patterns. The collectivity and social cohesiveness among people occurred because of their ability to use adaptation or integration strategy. Both Muslim and Aboge communities have high intercultural communication competence, so they are able to dwell in unity and help each other most of the time.